Multidisciplinary understanding of modifiable physical disability risk factors for health professionals: A scoping review protocol. - Derek Hanson; Stephen Samendinger; Edwin McCulley (PLoS ONE)
Introduction Physical disability represents a major burden to health and lifespan, particularly as the proportion of older adults within the United States is expected to grow. Prevention efforts for physical disability targets methods and strategies to decrease modifiable risk factors. Potential challenges for health professionals may exist in synthesizing and interpreting this broad spectrum of literature due to the discipline-specific nuance of language used, practice type or specialty, and lack of interdisciplinary resources. This scoping review will map and synthesize the literature across healthcare disciplines to identify modifiable risk factors and the evidence related to their ability to predict physical disability. We will also draw attention to the possibility of modifiable risk factors for physical disability being operationalized as pre-disability in order to strengthen primary and secondary prevention efforts. Methods A planned search strategy using physical disability terminology will be searched in English across MEDLINE, CINAHL, Health Source, PEDro, and REHABDATA by two reviewers in line with our review objectives and inclusion criteria. Eligibility for inclusion include peer-reviewed primary research published in the English language and have established a relationship between a person-level measurable characteristic that is modifiable by changes in lifestyle behaviors and any of the commonly accepted terms used to categorize or describe physical disability. Expected results Presentation of results will be using the PRISMA flowchart, with additional mapping and synthesis of evidence for modifiable risk factors for physical disability to clarify divergent terms used in classifying and measuring these factors and their potential for prediction of physical disability. Expected conclusion It is anticipated that this scoping review will identify and highlight a variety of modifiable risk factors for physical disability that may aid primary and secondary prevention efforts for health professionals.